IMPLEMENTASI PROGRAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA SEKOLAH MENENGAH PERTAMA NEGERI (SMPN) 7 KOTA PASURUAN - Danastri Putri Wardani (Halu Oleo University, 2024)
In accordance with the New Curriculum approved by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) during the leadership of Mr. Nadiem Makarim the Pancasila Student Profile Enhancement Project (P5). The aim of this research is to be able to know the implementation of the project of strengthening the profile of students' Pancasila that is implemented in the First High School of the State 7 City of Pasuruan. The researchers used the kind of research qualitative descriptive method. This study uses David C. Korten's theory that there are three indicators. The results of the research showed the implementation of the project student profile strengthening program Pancasila was very helpful in shaping the character of students and already in the category both on program indicators, implementing organizations, and target groups.